Intraoperative Assessment of Mid-Flexion Instability in Primary Total Knee Replacement (Journal of Pakistan Orthopaedic Association, 2019)
Introduction: Midflexion instability in primary total knee replacement (TKR) is an evolving concept. Successful treatment of instability requires an understanding of the different types of instability.Methods: A literature review was performed to identify information pertinent to midflexion instability in primary total knee replacement, utilising some guidelines.Results: Three factors, i.e., elevated joint line, multiradii femoral component and medial collateral ligament (MCL) laxity, were identified to influence midflexion instability. Literature suggested mediolateral instability at 30–60° of flexion as diagnostic of midflexion instability. Literature search also revealed paucity in clinical studies analysing midflexion instability. Most of the evidence was obtained from cadaveric studies for elevated joint line and MCL laxity. Clinical studies on multiradii femoral component were limited by their small study size and early followup period.Conclusion: Elevated joint line, multiradii femoral component and MCL laxity have been suggested to cause midflexion laxity in primary TKR. Due to limitations in available evidence, this review was unable to raise the strength of overall evidence. Future well-designed clinical studies are essential to make definitive conclusions. This review serves as a baseline for future researchers and creates awareness for routine assessment of midflexion instability in primary total knee replacement.